2019
DOI: 10.1155/2019/8324596
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Activity of Cordia africana (Lam.) (Boraginaceae) Leaf Extracts and Solvent Fractions in Plasmodium berghei-Infected Mice

Abstract: Background. Malaria remains a major worldwide public health problem leading to death of millions of people. Spread and emergence of antimalarial drug resistance are the major challenge in malaria control. Medicinal plants are the key source of new effective antimalarial agents. Cordia africana (Lam.) is widely used for traditional management of malaria by local people in different parts of Ethiopia. The present study aimed to evaluate in vivo antimalarial effects of leaf extracts and solvent fractions of Cordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…As a result, alkaloids, anthraquinones, phenol, tannins, and flavonoids found in this fraction may have attributed to the discovered antimalarial activity. Alkaloids [ 57 ], flavonoids [ 58 ], phenols [ 59 ], anthraquinones [ 60 ], and tannins [ 61 ] have all been implicated with antimalarial activity. This outcome is concordant with the efficacy of CF reported on CF of Brucea antidysenterica leaves [ 62 ], but higher with the low effect of CF reported on root of Silene macrosolen A.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, alkaloids, anthraquinones, phenol, tannins, and flavonoids found in this fraction may have attributed to the discovered antimalarial activity. Alkaloids [ 57 ], flavonoids [ 58 ], phenols [ 59 ], anthraquinones [ 60 ], and tannins [ 61 ] have all been implicated with antimalarial activity. This outcome is concordant with the efficacy of CF reported on CF of Brucea antidysenterica leaves [ 62 ], but higher with the low effect of CF reported on root of Silene macrosolen A.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the concentrated aqueous solution filtrate was placed in a deep freezer overnight followed by drying with a lyophilizer set at −50°C to remove water. Finally, the percentage yield of the crude extract was calculated and kept in an airtight container at −20°C until used for the intended experiment [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…is one of the most common forest tree species in the family. Locally, it is known as wanza and is commonly named as East African Cordia or large-leafed Cord17a or Sudan teak in English [ 13 ]. It is found in the moist evergreen highlands and riverine forests of the northwest and southwest highlands and is very common in western Ethiopia between 550 and 2600 m where the rainfall range is 700 to 2000 mm per year [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A botanical study conducted in northwestern Ethiopia reported that Cordia africana was traditionally used to treat liver disease, dysentery, stomach pain, and diarrhea (8) . The dried leaf powder is used to treat malaria and its associated symptoms by traditional healers (9) . Klebsiella species are routinely found in the human nose, mouth, and gastrointestinal tract as normal flora; however, they can also behave as opportunistic human pathogens , it can lead to a wide range of disease states, notably pneumonia, urinary tract infections, sepsis, meningitis, diarrhea, peritonitis and soft tissue infections it may be treated by leaves of Cordia leucocephala, popularly known as "Maria Brita", are used as an infusion to treat dysmenorrhea (10,14) .…”
Section: Introductionmentioning
confidence: 99%